Molecular Gymnastics: Mechanisms of HIV-1 Resistance to CCR5 Antagonists and Impact on Virus Phenotypes - Roche, Michael; Borm, Katharina; K. Flynn, Jacqueline; R. Lewin, Sharon; J. Churchill, Melissa; R. Gorry, Paul (Current Topics in Medicinal Chemistry, 2016)
Human immunodeficiency virus type 1 (HIV-1) enters host cells through the binding of its envelope glycoproteins (Env) to the host cell receptor CD4 and then subsequent binding to a chemokine coreceptor, either CCR5 or CXCR4. CCR5 antagonists are a relatively recent class addition to the armamentarium of anti-HIV-1 drugs. These compounds act by binding to a hydrophobic pocket formed by the transmembrane helices of CCR5 and altering the conformation of the extracellular domains, such that they are no longer recognized by Env. Maraviroc is the first drug within this class to be licenced for use in HIV-1 therapy regimens. HIV resistance to CCR5 antagonists occurs either through outgrowth of pre-existing CXCR4-using viruses, or through acquisition of the ability of CCR5-using HIV-1 to use the antagonist bound form of CCR5. In the latter scenario, the mechanism underlying resistance is through complex alterations in the way that resistant Envs engage CCR5. These significant changes are unlikely to occur without consequence to the viral entry phenotype and may also open up new avenues to target CCR5 antagonist resistant viruses. This review discusses the mechanism of action of CCR5 antagonists, how HIV resistance to CCR5 antagonists occurs, and the subsequent effects on Env function.
Keywords: Envelope